Volatile Constituents of the Seed Kernel and Leaf of Moringa peregrina (Forssk.) Fiori, Agricolt. Cultivated in Chabahar (Iran): Volatile constituents of the seed kernel and leaf of Moringa peregrina - Suleiman Afsharypuor; Gholamreza Asghari; Abdolali Mohagheghzadeh; Shadab Dehshahri (Iranian Journal of Pharmaceutical Sciences, 2010)
Volatile constituents of the seed kernel and leaf of cultivated Moringa peregrina (Forssk.) Fiori, Agricolt collected after hydrolysis were analyzed by GC and GC/MS. Five glucosinolate degradation products which constituted almost the whole isolated oil of the seed kernel were identified to be: isobutyl isothiocyanate (94.0%), isopropyl isothiocyanate (4.9%), sec-butyl isothiocyanate (0.5%), n-butyl isothiocyanate(0.5%) and benzyl isothiocyanate (<0.1%); while the volatile isothiocyanates which constituted also almost the whole isolated oil of the leaf were found to be: isobutyl isothiocyanate (88.5%), isopropyl isothiocyanate (10.2%), n-butyl isothiocyanate (0.4%) and sec-butyl isothiocyanate (<0.1%).